The Inclusion, Diversity, Equity and Accessibility audit. A post-occupancy evaluation method to help design the buildings of tomorrow. (1st June 2022) - Zallio, Matteo; Clarkson, P. John
Abstract: Notwithstanding the increased number of regulations there is a general lack of awareness about Inclusive Design among building industry professionals. This is partly due to the scarcity of available tools to evaluate occupancy feedback on inclusion, diversity, equity and accessibility. How can we implement a tool to evaluate occupancy feedback on inclusion, diversity, equity and accessibility that works for the building industry? This study aims to inform the development of a post-occupancy method to evaluate Inclusion, Diversity, Equity and Accessibility (IDEA) in the built environment. This article reports the results of a multifaceted Delphi study which culminated with co-designing the IDEA audit, a post-occupancy evaluation method to collect data on people's perceptions of inclusion, diversity, equity and accessibility. With the IDEA audit, researchers, building owners, design teams, developers, facility managers, tenants, and organisation leaders can achieve a baseline of understanding of what people feel in regard to inclusion, diversity, equity and accessibility, clearly identify pockets of inconsistency and use data to decide how to address challenges and points of exclusion. Highlights: Inclusive Design is not widely adopted in architectural design practice. There is scarcity of post-occupancy evaluation methods on inclusion and accessibility. Mapping building occupant's perception of inclusion and accessibility is key to design inclusively. Mixed method evaluation can help professionals to understand points of exclusion in the building. The IDEA audit helps to understand people's perception of inclusion and accessibility.